The benefits of changing the marriage age limit in the marriage law from the perspective of Islamic law - Firdausiyah, Vita (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
Marriage is a sacred institution governed by Islamic law and national marriage law. Previously, the minimum age for marriage was regulated in Article 7 Paragraph (1) of Law Number 1 of 1974, allowing men to marry at 19 and women at 16. However, this regulation was deemed irrelevant to the principle of maslahah in Islamic law, which aims to promote benefits and prevent harm. Consequently, the government enacted Law Number 16 of 2019, which raised the minimum marriage age for women to 19 years. This study aims to analyze the impact of the age limit changes introduced by Law Number 16 of 2019 from the perspective of maslahah in Islamic law. The research method employed is library research with a normative juridical approach, using primary sources such as the Qur'an, Hadith, fiqh principles, Law Number 16 of 2019, and Constitutional Court Decision Number 22/PUU-XV/2017. The findings reveal that the changes have philosophical, sociological, and juridical implications. Philosophically, they reflect the state's commitment to eliminating discriminatory practices. Sociologically, the changes have led to an increase in marriage dispensation requests in Religious Courts. Juridically, the amendments align with the principles outlined in the Compilation of Islamic Law (KHI) and Law Number 1 of 1974. From the maslahah perspective, the revised law upholds the protection of religion, life, lineage, intellect, and property while contributing to national goals, including economic growth, poverty reduction, and the protection of children's rights.